Sclerotherapy in the Treatment of Familial Disseminated Cutaneous Glomuvenous Malformations: Case Report - Francisco Gil; Santiago Ortiz; João Aranha (Sociedade Portuguesa de Dermatologia e Venereologia, 2019)
Glomuvenous malformations usually present as soft bluish-purple dermal or subcutaneous papules, nodules or plaques, and can occur as sporadic or inherited lesions. We present the case of a 41-year-old female, referred for evaluation of disseminated bluish lesions developing since puberty. Histopathology was consistent with the diagnosis of glomuvenous malformations. The history of a sister with similar lesions justified a genetic study of the glomulin gene that revealed a pathogenic mutational variant allowing the diagnosis of familial disseminated cutaneous glomuvenous malformations. Whereas surgical management is often used for symptomatic solitary lesions of glomuvenous malformations, other treatment modalities have been reported for treatment of multiple lesions, with variable results. The patient underwent sclerotherapy with polidocanol and there were significant symptomatic and cosmetic improvements after six sessions, with no adverse effects and no recurrence after 6 months.